The Styles and Paradigms of the Evaluations Made by School Teachers [Estilos y Paradigmas Evaluativos en Docentes de Educación Escolar] - Rios-Munoz, D; Salinas-Fritz, P; Herrera-Araya, D (Pontificia Universidad Javeriana, 2022)
he aim of this study is to discuss the styles of the evaluation of students and describe their characteristics in terms of the paradigms of evaluation used by school teachers in Santiago, Chile. It used a mixed method. A questionnaire about their styles of evaluation was completed by 54 teachers at three schools: it was complemented by a group interview. The results show that teachers combine two styles of evaluation – one formal and analytic, the other, tolerant and guiding. This reflects an integration of a positivist and naturalist scheme of evaluation. To conclude: the findings point to the conflict the teachers feel about the contrast between the standardized methods and the true purposes of such evaluations. © 2022 Pontificia Universidad Javeriana. All rights reserved.